HERMENEUTICS OF NATIONALITY FIQH: STUDY OF BAHTSUL MASAIL OF LIRBOYO ALUMNI ASSOCIATION - Iis Kholilah (Khazanah: Jurnal Studi Islam dan Humaniora, 2019)
This article analyses the text of bahtsul masail from the alumni of Lirboyo Islamic traditional boarding school focusing on the motive behind its publication, the basic concept of nationalism proposed by the text, the dominance of legal reasoning used in the text and its potential toward the readers. By employing critical hermeneutic approach, there were three stages of analysis, i.e. socio-historical analysis, text analysis and interpretation of the text. According to the analysis this research concludes that the recent phenomenon of the rising of anti-nationalism Islamic movement led by Hizbut-Tahrir and certain radical hard-line organization since 2000s has been the main motive of the publication of the text. This text also proposes the meaning of nationalism as the intention to love the nation and country and its consequences as a Moslem in Indonesian context. Moreover Qauliyah has had been used as the main legal reasoning to formulate certain concepts and this text might be less compatible for the prospective readers outside the Santri’s community. Because many arguments from Arabic resources scattered throughout the text in which still need depth explanation for the beginners.